2009
DOI: 10.1590/s1516-44462009000100013
|View full text |Cite
|
Sign up to set email alerts
|

Review of the efficacy of placebo in comparative clinical trials between typical and atypical antipsychotics

Abstract: Review of the efficacy of placebo in comparative clinical trials between typical and atypical antipsychotics Revisão da eficácia do placebo nos ensaios clínicos que comparam antipsicóticos típicos e atípicos , "aripiprazole", "clozapine", "olanzapine", "quetiapine", "risperidone", "sertindole", "ziprasidone" and "zotepine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…However, we noted a 43% improvement in manic symptoms in the individuals with BSD treated with Vitamin D 3 , which compares favorably with the 20% improvement usually seen with placebo (Oliveira et al 2009). We also had a relatively small sample size.…”
Section: Limitations and Future Considerationssupporting
confidence: 54%
“…However, we noted a 43% improvement in manic symptoms in the individuals with BSD treated with Vitamin D 3 , which compares favorably with the 20% improvement usually seen with placebo (Oliveira et al 2009). We also had a relatively small sample size.…”
Section: Limitations and Future Considerationssupporting
confidence: 54%
“…Atypical antipsychotics are as effective as typical antipsychotics and have reduced the incidence of extrapyramidal side effects, including akathisia, dystonia and tardive dyskinesia. 17,32 Of the atypical agents, two currently have an IM form available: olanzapine (Zyprexa®) and ziprasidone (Geodon®). Both are at least as effective as haloperidol at producing rapid tranquilization in acutely agitated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Atypical antipsychotics may be associated with prolongation of the QT interval and sudden cardiac death, and appropriate precautions should be taken when administering the drug. 17,33 Although some trials have provided limited evidence for a superior speed of onset 34,35 or degree of response, 32,34,36 other studies have demonstrated similar results between first-generation and second-generation antipsychotics (SGA). 10,37 Moreover, other studies have not consistently demonstrated the superior efficacy of SGA compared to haloperidol alone.…”
Section: Discussionmentioning
confidence: 99%
“…Atypical neuroleptic drugs are currently widely used in treating dementia accompanied by neuropsychiatric symptoms in AD due to fewer adverse reactions compared with typical antipsychotics [Oliveira et al, ]. In addition, atypical neuroleptics have seen an increase in clinical use due to some documented evidence that they improve psychological and behavioral symptoms in AD [Lopez et al, ].…”
Section: Current State Of Intervention For Neuropsychiatric Symptoms mentioning
confidence: 99%